Absorption and fluorescence studies of new 3-amino-N-(2-hydroxy-, (3-hydroxypropoxy)- or (3-chloropropoxy)-5-(propylamino)-9H-benzo[a]phenoxazin-9-ylidene)propan-1-aminium chlorides - Firmino, A. D. G. (2012)
In recent years, fluorescence techniques have seen an enormous improvement, being in nowadays an interesting tool in the visualization and quantification of biomolecules, frequently used in cell biology, biochemistry, proteomics, immunochemistry, flow cytometry and medical diagnostics.1 Although intrinsic fluorophores are of great interest, the development of new extrinsic fluorophores is crucial for the design of new fluorescent probes, namely with improved water solubility, functional groups, and enhanced fluorescence quantum efficiency at high emission wavelengths.2 As a continuation of our previous research,3 this communication describes the evaluation of absorption and emission properties of new mono- and bifunctionalised benzo[a]phenoxazinium chlorides 1a-c in ethanol, water, and at simulated physiological pH, focus on the variation of the concentration. In order to investigate the sensitivity of fluorescence of the long-wavelength fluorophores to pH, photophysical studies under controlled pH also were performed.